2019
DOI: 10.5005/jp-journals-10024-2666
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Advanced Platelet-rich Fibrin on Wound Healing after Third Molar Extraction: A Split-mouth Randomized Double-blind Study

Abstract: Aim: To evaluate the potential of advanced platelet-rich fibrin (A-PRF) as a regenerative biomaterial for bone regeneration and postoperative sequelae after impacted third molar extractions. Materials and methods: This was a split-mouth, randomized, double-blind clinical trial. A total of 10 female patients in King Abdulaziz University Dental Hospital with bilateral impacted third molars were recruited into the study. Surgical extractions were performed on both sides of the mandible. Randomization was done by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
2
26
0
Order By: Relevance
“…Results of the present study is in accordance with that of many investigators (23)(24)(25)(26) who found that grafting the distal to mandibular second molars resulted in a significant reduction in the probing pocket depth and clinical attachment level gain and in disagreement with Tabrizi et al (27) and Zahid and Nadershah (15) who found no difference in PD and CAL between the grafted and no grafted groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Results of the present study is in accordance with that of many investigators (23)(24)(25)(26) who found that grafting the distal to mandibular second molars resulted in a significant reduction in the probing pocket depth and clinical attachment level gain and in disagreement with Tabrizi et al (27) and Zahid and Nadershah (15) who found no difference in PD and CAL between the grafted and no grafted groups.…”
Section: Discussionsupporting
confidence: 91%
“…In spite of the great advantages of PRF in healing process, PRF single use seems to have no beneficial role in bone healing and have no effect on the periodontal status of the lower second molars after extraction of the mandibular third molars. The findings of Zahid and Nadershah (15) study demonstrated that A-PRF successfully act as a potential biomaterial for lessening the severity of pain and swelling after third molar surgery. They concluded that long-term trials with a larger sample size and more methodically sound assessment tools are needed to obtain more meaningful results on periodontal regeneration.…”
Section: Discussionmentioning
confidence: 92%
“…The authors emphasize that the incorrect assessment of pain may have been influenced by the fact that the procedures in all patients were performed bilaterally during one visit [ 37 ]. Zahid and Nadershah [ 38 ] performed a similar study. A statistically significant reduction in the pain was observed in the A-PRF side compared with the controls.…”
Section: Discussionmentioning
confidence: 99%
“…In some articles, there was an efficient control with PRF for the items pain, edema, trismus, and bone repair accelerator (Zahid & Nadershah, 2019;Yüce & Kömerik, 2019;Kapse et al, 2019;Daugela et al, 2018;Kumar et al, 2015). However, some studies reported no significant effect in controlling pain, edema, and postoperative trismos (Torul et al, 2020;Ritto et al, 2019;Asutay et al, 2017) although the acceleration of tissue repair in the region is evident.…”
Section: Platelet-rich Fibrin/platelet Rich Plasmamentioning
confidence: 99%
“…The articles that rated the effectiveness of platelet concentrates in controlling of postoperative pain in third molar surgery were the ones that presented the most significant amount of risk of bias. The small number of patients studied (Zahid & Nadershah, 2019) and the lack of an adequate placebo control group were some of them (Caymaz & Uyanik 2019;Afat et al, 2018). Although several studies on platelet concentrates on third molar surgery, the vast majority have been about socket healing, edema, and pain.…”
Section: Platelet-rich Fibrin/platelet Rich Plasmamentioning
confidence: 99%